Answer:
The value of the expression given is:
Explanation:
First, you must divide the expression in three, and to the final, you can multiply it:
- [(3^8)*(2^(-5))*(9^0)]^(-2)
- [(2^(-2))/(3^3)]^4
- 3^28
Now, we can solve each part one by one:
First part.
- 3^8 = 6561
- 2^(-5) = 0.03125
- 9^0 = 1 (Whatever number elevated to 0, its value is 1)
- (6561 * 0,03125 * 1) = 205.03125
And we elevate this to -2:
- 205.03125^-2 = 2.378810688*10^(-5) or 0.00002378810688
Second part.
- 2^(-2) = 0.25
- 3^3 = 27
- 0.25 / 27 = 9.259259259 * 10^(-3) or 0.00925925925925
And we elevate this to 4:
- 0.00925925925925^4 = 7.350298528 * 10^(-9) or 0.000000007350298528
Third Part.
- 3^28 = 2.287679245 * 10^13 or 22876792450000
At last, we multiply all the results obtained:
- 0.00002378810688 * 0.000000007350298528 * 22876792450000 = 3.999999999999999999 approximately 4
We approximate the value because the difference to 4 is minimal, which could be obtained if we use all the decimals in each result.